Trends and Developments in Gamification for Science Education: A Bibliometric Review from 2019 to 2023 - Amri Saputra; Umi Hijriyah; Listiyani Siti Romlah; Agus Susanti; Sunarto; Qonita Shabira (Postgraduate, University of Mataram, 2025)
This study aims to identify and analyze research trends in gamification focusing on science education and explore opportunities for further development. Using the Systematic Literature Review (SLR) method, a total of 126 relevant publications were identified from the Publish or Perish database indexed by Scopus, with 43 documents from the 2019–2023 period selected and analyzed based on inclusion criteria. These criteria include articles discussing gamification in science education, English-language articles, open-access publications, and Scopus-indexed articles. The literature review process followed PRISMA guidelines to ensure the quality of results, and data were analyzed using bibliometric methods with the assistance of VOSviewer 1.6.20 software. The results indicate significant fluctuations in the number of publications and citations year by year, reflecting the dynamics of research activity. Most publications originate from Spain, the United States, and Malaysia, with quantitative methods being the most widely used approach (51%). The main themes explored include student engagement, motivation, and conceptual understanding, particularly in STEM subjects. Collaborative networks highlight the importance of diverse perspectives in advancing gamification research. Density analysis reveals that the long-term impact and scalability of gamification in educational science still hold substantial potential for exploration. Therefore, further studies are urgently needed to optimize the role of gamification and maximize its benefits in the learning process.